Ecumenical search for truth and the identity of the Christian Church - Dulskis, Romualdas (Religija ir kultūra, 2007)
Ecumenism should not be understood as an aspiration for merely external and superficial unity. Ecumenical dialogue is a dialogue of conversion. This dialogue is being executed in the face of God, and so each participant is invited to seriously check his/her conscience, make bold to acknowledge his/her wrongness, confess his/her faults and take the road of truth, justice and good. Ecumenical efforts are understood not as a man-thought of scope but as a work inspired by the Holy Spirit and God’s grace for the modern Church and the world.Ecumenism is tolerant to diverse theological thinking, different aspects of Christian practice and various forms of religious cults, but at the same time ecumenism urges people to accept the plenitude of God’s truth and goodness into their hearts and life. One of the main goals of the ecumenical movement is to bring a human being into face-to-face with the Gospel and the objective divine truth. Ecumenism encourages us to plead guilty not only to our sins but also to any dishonesty regarding the divine truth and our reticence to the divine truth by taking inspiration from the Holy Spirit.Aspirations to convert the divine truth into the subjective in every person’s truth are also a denial of objective harmonic development of a human being. Thus, the subjective truth leads one to subjectively perceive good that can often be destructive or evil and so destroying both personal harmony and the harmony of social life. That is why for today’s Christians and all people of good-will there no other way but to expand their hearts and find themselves as creatures that can be satisfied only by recognition of the divine truth and divine goodness, as well as their implementation in all dimensions of the daily rounds of living.
Keywords: Church; truth; ecumenism; priesthood of the laity